Stance nouns in argumentative essays by L2 Malaysian undergraduates - Teh, Hui Lin; Lee, Geok Imm; Nimehchisalem, Vahid; Abdullah, Ain Nadzimah (Penerbit Universiti Kebangsaan Malaysia, 2025)
Stance nouns are an important feature of academic writing since they indicate to the readers how writer’s stance and the arguments are to be interpreted. However, there is a lack of studies in investigating how the L2 undergraduate students use stance nouns in L2 argumentative writing. With the aim to gain more insights into patterns of use of stance nouns in L2 academic writing, this study employed summative content analysis to analyse the patterns of stance nouns in 100 argumentative essays by the L2 first-year undergraduate students in a private university in Malaysia. Based on the classification of stance nouns model by Jiang and Hyland (2015), the frequencies of the three types of stance nouns (entity, attribute and relation) were identified to determine the patterns of use of the stance nouns. The findings show that L2 students used more manner nouns and status nouns (attribute type), and event nouns (entity type) that reflected more epistemic evaluations and evidence-based reasonings in their stance. The classification of stance nouns indicates how writers use them to express stance and influence how readers interpret the arguments presented. In conclusion, different variants of stance nouns can help writers to strengthen their arguments in argumentative writing. This may inform the development in corpus-based teaching materials as the findings on patterns of use of stance nouns can be used as examples in the teaching and learning of argumentative writing.